2017
DOI: 10.1017/s0144686x16001495
|View full text |Cite
|
Sign up to set email alerts
|

Living arrangements of community-dwelling older Singaporeans: predictors and consequences

Abstract: In this paper, we examine predictors and consequences of living arrangements among community-dwelling older Singaporeans. We take a holistic approach and consider a range of social and economic as well as emotional and physical wellbeing indicators. Two waves (2009, 2011) of the Panel on Health and Ageing of Singaporean Elderly (PHASE) are analysed to (a) provide an overview of living arrangements in 2009 and assess the extent to which living arrangements change by 2011; (b) examine the predictors of living ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Either by choice or circumstance, an older person's preference in living arrangements is widely accepted to be affected by health outcomes. 22,59 In Asia, families have traditionally been and continue to be the primary source of care and support for older persons. It is just as likely that older adults with declining cognitive function may live with their children and families to receive better care and support as they age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Either by choice or circumstance, an older person's preference in living arrangements is widely accepted to be affected by health outcomes. 22,59 In Asia, families have traditionally been and continue to be the primary source of care and support for older persons. It is just as likely that older adults with declining cognitive function may live with their children and families to receive better care and support as they age.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Conversely, other studies have found that older Asian adults are more likely to be in poor physical and cognitive health when living with their adult children. 22,23 However, little research has examined how living in large family households (i.e. with both children and grandchildren) affects cognitive health in old age.…”
Section: Introductionmentioning
confidence: 99%
“…There are different assessments for functional ability. Most studies assessed functional abilities with BADLs [36][37][38], measured with basic activities, such as eating and toileting.…”
Section: Discussionmentioning
confidence: 99%
“…The expression "living arrangements" refers to the number of people who form a family unit and the generation relations that exist among them (1) . Recently, the characteristics and determining factors of senior citizens' living arrangements have been the target of many studies, since they have important implications for wellbeing and the social interaction, and can define the exposure of the seniors to risk factors, as well as their access to health protection (2) .…”
Section: Introductionmentioning
confidence: 99%
“…Researches have shown that situations in which the elder lives with other members of the family are related to factors such as culture, health conditions of the elder, social support network, and economic situation. These studies show that there are many different living arrangements according to these factors (1)(2)(3) . Living with a spouse has been considered as one of the most beneficial living arrangements when it comes to the emotional and physical wellbeing of the elder (3)(4) .…”
Section: Introductionmentioning
confidence: 99%